Learn from the Australian experience - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Sustainable Crop Production in the Sub-tropics ISBN 0 7242 5985 6, 376 pp. Australian $95.